2021
DOI: 10.3390/ijms22052776
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Lipid Droplets with the Intracellular Transport Machinery

Abstract: Historically, studies of intracellular membrane trafficking have focused on the secretory and endocytic pathways and their major organelles. However, these pathways are also directly implicated in the biogenesis and function of other important intracellular organelles, the best studied of which are peroxisomes and lipid droplets. There is a large recent body of work on these organelles, which have resulted in the introduction of new paradigms regarding the roles of membrane trafficking organelles. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 117 publications
(155 reference statements)
0
9
0
Order By: Relevance
“…Vesicle trafficking is an important process for steroidogenesis. For instance, the life cycle of lipid droplets, which are a source of cholesterol substrate for steroid hormones [ 21 ], involves intracellular trafficking (reviewed in [ 22 ]). The significant and rapid changes in Dymeclin protein levels in response to Fsk and Fsk+AICAR suggest that Dymeclin might play an active role in hormone-regulated steroidogenesis in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…Vesicle trafficking is an important process for steroidogenesis. For instance, the life cycle of lipid droplets, which are a source of cholesterol substrate for steroid hormones [ 21 ], involves intracellular trafficking (reviewed in [ 22 ]). The significant and rapid changes in Dymeclin protein levels in response to Fsk and Fsk+AICAR suggest that Dymeclin might play an active role in hormone-regulated steroidogenesis in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…42 In eukaryotes cells, the site of biogenesis of LDs is the phospholipid bilayer of the ER. 38,[43][44] As triacylglycerol's are biosynthesised within the ER they accumulate within its bilayer leading first to the budding and then monolayer enclosing of a LD. 38 This phospholipid monolayer provides structural integrity and stability to the LD in the cell.…”
Section: Cell Imaging With Np1-p188mentioning
confidence: 99%
“…In experimental models of NAFLD, cholesterol is more associated with large than small LDs in hepatocytes [ 15 , 16 ]. The size of LDs after their formation depends on very complex mechanisms including their catabolism through lipolysis and different types of lipophagy, their eventual fusion and, probably, also lipid synthesis on their surface [ 10 , 17 , 18 , 19 , 20 ]. Patatin-like phospholipase domain protein 3 (PNPLA3) is one lipolytic enzyme in hepatocytes located on large lipid droplets and several studies have shown that the PNPLA3 rs738409 (I148M) variant is powerfully linked to hepatic damage in NAFLD, at different levels such as steatosis, necroinflammation and fibrosis [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of steatotic hepatocytes in the liver and the size of LDs in each steatotic hepatocyte are determined not only by the imbalance between lipid supply and utilization/secretion but also by the amount/activity of regulatory surface proteins, including PNPLA3, and of lysosomal enzymes, which can differ in the hepatocytes of the same liver [ 17 , 20 , 21 , 27 , 28 , 29 , 30 ]. As a result, in the same human liver, heterogeneous populations of hepatocytes with and without steatosis can coexist, and, among the former, sometimes the size of the LDs is uniform, or some hepatocytes may contain large and others small LDs.…”
Section: Introductionmentioning
confidence: 99%